PENINGKATAN KOMPETENSI TAMTAMA BRIMOB POLDA JATIM MELALUI PENDIDIKAN PENGEMBANGAN SPESIALISASI - Bambang Wijaya, Bambang Wijaya; Oscarius Yudhi Ari Wijaya, Oscarius Yudhi Ari Wijaya (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
Abstract The reasons behind the author writing this Thesis with the Title “Competency Improvement for Enlisted Mobile Brigade of East Java Regional Police through Education and Specialization Training” are because the Enlisted Mobile Brigade of East Java Regional Police still lacks the understanding, lacks the competency for the position assigned now as well as the author’s curiosity to know how far the competency improved when the members of the Enlisted Mobile Brigade while in service. This Qualitative Research tries to describe and identify the steps and factors that are the hurdles in improving competency for Enlisted Mobile Brigade of East Java Regional Police through education and specialized training. The research is done by doing observation, interview, literature study from the human resources bureau of East Java Regional Police, the leadership element and staff in the Mobile Brigade Unit who have the authority related to education and personnel training of the enlisted as well as several enlisted personnel from the East Java Regional Police Mobile Brigade. The Enlisted Mobile Brigade of East Java Regional Police Competency Improvement apparently is stagnant. The result was obtained from observation, interview as well as literature study with informants saying that they only serve as the policy executor with limited processes. The Enlisted personnel in the Mobile Brigade Unit have not done the education and training yet. The factors causing the hurdles are there exists policy from the authorized official in determining which personnel can participate in education and training as well as the lack of budget. As a result of this research findings, the author concludes that the Competency Improvement of Enlisted Mobile Brigade of East Java Regional Police through education and specialized training is not happening because until now there is still no Enlisted personnel attend the education and training, due to the lack of understanding from the officials who have authority to execute the education and training, especially related to the involvement of the enlisted personnel. Hence, the author suggests that the Enlisted personnel to be involved in the education and training processes at the Mobile Brigade Unit and to do evaluation and coordination between the Human Resources Bureau of East Java Regional Police with the authorized officials in the Mobile Brigade Unit relating to the involvement of the enlisted personnel to attend the education and training